THE Pengaruh pendidikan, penduduk, pencari kerja terhadap kesempatan kerja di Jawa Barat 1985-2020 - Meilita Tri Rezeki; Lucia Rita Indrawati (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
Such a rapid growth in the labor force will have an impact on the economy, among others, on the expansion or creation of jobs. The lack of labor that is unable to accept the new labor force means that the increasing demand for the number of workers looks much less than the supply of the number of the labor force. This study aims to determine the influence of education, population, and job seekers on the employment opportunities of West Java Province in 1985-2020. Data quantitatif with multiple linear regression analysis and the Autoregressive Distributed Lag (ARDL) approach is the research method used. The research has proven that education variables have a significant positive effect on job opportunities, population variables have a negative and significant effect, and job seeker variables have a significant positive effect on job opportunities.